Protein intake as a determinant factor of physical activity in older persons - Kusumaratna, Rina K.; Hidayat, Adi (Universa Medicina, 2011)
Worldwide, the proportion of people aged 60 and over is growing faster than any other age group. It has been well-established that the aging process can be associated with increased susceptibility to chronic conditions, disability, and co-morbidity, which however may be minimized or even partially reversed by physical activity. The assessment of physical activity is becoming an increasingly important component in the evaluation of elderly persons. Nutritional intake and status play an essential role in determining the physical activity level potentially capable of minimizing the health burden of older persons. The objective of this study was to find out whether nutritional intake and status were correlated with physical activity in community-dwelling older persons. The study population included 219 aged 60 to 69 years, of whom complete measures of socio-demographic characteristics, nutritional status, nutritional intake and physical activity were obtained. Serum total protein, albumin, globulin and hemoglobin concentration were measured as nutritional indicators (biomarkers). The nutrient content of food intakes was analyzed and calculated by â€œNutrisurveyâ€ software. Analysis indicated that there was a significant correlation between nutritional biomarkers [total protein (r=-0.211; p=0.002) and globulin (r=-0.247; p=0.000)] and physical activity. Compared to other food intakes, intakes of carbohydrate (r=0.241; p=0.001) and animal protein (r=0.149; p=0.027) were significantly correlated with physical activity. Our findings lend support to the existence among healthy older persons of a relationship between nutrional intake and status and physical activity.